Global Stability of an Eco-Epidemiological Model with Time Delay and Saturation Incidence - Shuxue Mao; Rui Xu; Zhe Li; Yunfei Li (Discrete Dynamics in Nature and Society)
We investigate a delayed eco-epidemiological model with disease in predator and saturation incidence. First, by comparison arguments, the permanence of the model is discussed. Then, we study the local stability of each equilibrium of the model by analyzing the corresponding characteristic equations and find that Hopf bifurcation occurs when the delay τ passes through a sequence of critical values. Next, by means of an iteration technique, sufficient conditions are derived for the global stability of the disease-free planar equilibrium and the positive equilibrium. Numerical examples are carried out to illustrate the analytical results.